Pareceristas deste volume - tempos, outros (Outros Tempos: Pesquisa em Foco - História, 2010)
Adriana Maria de Souza Zierer (UEMA); Ana Maria Mauad (UFF); César Augusto Castro (UFMA); Cláudio Zannoni (UFMA); Elizabeth Sousa Abrantes (UEMA); Salânia Maria Barbosa Melo (UEMA); Sônia Maria de Meneses Silva (URCA); Carlos Alberto Ximendes (UEMA); Carlos Frederico Lago Burnett, (UEMA); Conceição Solange Bution Perin (FAFIPA); Dorval do Nascimento ( UFMA); Helidacy Maria Muniz Corrêa ( UEMA ); Júlia Constança Pereira Camêlo (UEMA); Magali Gouveia Engel (UFF); Moisés Romanazzi Tôrres (UFSJ); Nielson Rosa Bezerra (UEMA); Protásio Paulo Langer (UFGD); Regina Helena Martins de Faria (UFMA); Reinaldo dos Santos Barroso Júnior (UEMA); Rita de Cássia Pizzoli (FAFIPA); Sandra Regina Rodrigues dos Santos (UEMA); Terezinha Oliveira (UEM); Washington Tourinho Júnior ( UFMA); Yuri Michel Pereira Costa (UEMA.